The Literature Review: The Influence of Peer Conformity on Academic Procrastination among Students - Nisa Nur Afifah; Andre Julius; Syari Fitrah Rayaginansih (Ma'soem University, 2025)
This study is a literature review of 18 scientific sources, primarily from the Indonesian educational context, that examine the relationship between peer conformity and academic procrastination in Indonesian students. The results of the analysis show that conformity, as a form of social influence that encourages individuals to adjust to the values, norms, and behaviors of the group for social acceptance, has three main aspects: cohesiveness, agreement, and obedience. Meanwhile, academic procrastination is understood as the deliberate and repeated postponement of tasks that negatively impacts student achievement and well-being, involving behavioral and psychological aspects. The levels of peer conformity and academic procrastination among students are generally moderate, influenced by age, social context, and educational environment. A total of 84% of the literature shows a positive and significant influence of conformity on procrastination, while 16% state that it has no effect, indicating that other psychosocial factors need to be further examined.